2013
DOI: 10.1371/journal.pone.0057812
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peroxisome Proliferator-Activated Receptor γ in Immune Responses to Enteroaggregative Escherichia coli Infection

Abstract: BackgroundEnteroaggregative Escherichia coli (EAEC) is recognized as an emerging cause of persistent diarrhea and enteric disease worldwide. Mucosal immunity towards EAEC infections is incompletely understood due in part to the lack of appropriate animal models. This study presents a new mouse model and investigates the role of peroxisome proliferator-activated receptor gamma (PPARγ) in the modulation of host responses to EAEC in nourished and malnourished mice.Methods/Principal FindingsWild-type and T cell-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
13
1
Order By: Relevance
“…Asterisks (*) indicate statistical significance compared with uninfected mice and the number symbol (#) represents statistical difference compared with infected wild type mice (p < 0.05). 81 Modulating the parameters regulating T cell differentiation into separate phenotypes simulated PPARγ deficiency: Th1 and Th17 cell differentiation was enhanced equally while Treg differentiation was decreased in an equal magnitude. Bacterial clearance predicted in silico mimicked EAEC quantification in feces from infected mice (B).…”
Section: Future Perspective In Eaec Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asterisks (*) indicate statistical significance compared with uninfected mice and the number symbol (#) represents statistical difference compared with infected wild type mice (p < 0.05). 81 Modulating the parameters regulating T cell differentiation into separate phenotypes simulated PPARγ deficiency: Th1 and Th17 cell differentiation was enhanced equally while Treg differentiation was decreased in an equal magnitude. Bacterial clearance predicted in silico mimicked EAEC quantification in feces from infected mice (B).…”
Section: Future Perspective In Eaec Animal Modelsmentioning
confidence: 99%
“…73 Recently, our group published in vivo data reporting for the first time the importance of T helper (Th)17 cells in host responses to EAEC and EAEC clearance. 81 By pharmacologically and genetically disrupting the activity of the transcription factor peroxisome proliferator-activated receptor (PPAR) γ in malnourished mice, we modulated mucosal inflammation that resulted in enhanced Th17 phenotypes and disease amelioration ( fig. 1, first and fifth enterocytes, underlying mucosa).…”
mentioning
confidence: 99%
“…The cytokine can have both protective and pathogenic effects in different infection and inflammation models and organ systems (Onishi and Gaffen, 2010). In the intestinal tract, IL-17A is required for protective immunity against Helicobacter pylori (Algood, et al, 2009), Citrobacter rodentium (Ishigame, et al, 2009), Salmonella enterica serovar Typhimurium (Mayuzumi, et al, 2010; Raffatellu, et al, 2008), and enteroaggregative Escherichia coli (Philipson, et al, 2013), indicating that IL-17A is an important regulator of mucosal immune defenses associated with mucosal inflammation. Although Giardia infection is typically devoid of acute inflammatory events (Oberhuber, et al, 1997), a recent study found that IL-17A contributes to clearance of the murine pathogen Giardia muris (Dreesen, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The EAEC 042 genome was characterized in 2010, it is comprised by a circular chromosome of 5,241,977 bp and one plasmid of 113,346bp, known as the “aggregative adherence plasmid” (pAA)[12]. The other EAEC reference strain that has been used in animal models is JMM221, which has been particularly useful for understanding the EAEC immune response in malnourished mice [13]. …”
Section: Eaec History and Epidemiologymentioning
confidence: 99%